Evaluasi Kesesuaian Fasilitas Penyimpanan Obat di Puskesmas Gondomanan Kota Yogyakarta - Doni Saputra; Arina Titami; Yuni Andriani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Background: Drug storage regulates drugs received to be safe and free from physical or chemical damage, and their quality is guaranteed, per the established requirements. Improper drug storage in health centers can cause drug damage. Damaged drugs can hurt patients and health services themselves.Objective: To determine the suitability of drug storage facilities at the Puskesmas Gondomanan Kota Yogyakarta.Method: The research method used is descriptive non-experimental with a cross-sectional approach. The data needed in this study are observation data. Findings: The study results at Puskesmas Gondomanan Kota Yogyakarta showed that the drug storage facilities were 100% suitable. Conclusion: The suitability of drug storage facilities at the Puskesmas Gondomanan Kota Yogyakarta is by standards based on Permenkes RI Nomor 74 Tahun 2016 and Petunjuk Teknis Standar Pelayanan Kefarmasiaan di Puskesmas Tahun 2019.